Real‐world treatment patterns of patients with atopic dermatitis in Japan: Analysis of the JMDC Claims Database - Kazumasa Kamei (Wiley, 2021)
Abstract Objectives This study was conducted to assess changes in the real‐world treatment of atopic dermatitis (AD) in Japan. Methods Patients from the JMDC Claims Database with ≥1 confirmed diagnosis of AD, an identifiable medical care start date for AD, and ≥2 AD–related treatments on separate dates between January 1, 2005, and May 31, 2019, were included; data were analyzed on a yearly basis. Results In total, 411,102 patients were included. The average age of patients increased from 12.0 to 18.8 years between 2005 and 2017. In any given year, the prevalence of AD was highest in patients aged <2 years and lowest in patients aged ≥50 years. Dermatology (65.1%‐69.5% from 2005 to 2017) and clinics (92.3%‐93.4%) were the main department and medical facility, respectively, providing daily medical care for AD. The proportion of patients who were given the thymus and activation‐regulated chemokine test increased from 2008 to 2017 (0.03%‐3.5%). From 2005 to 2017, the proportion of patients who received moisturizer (68.8%‐79.1%), topical calcineurin inhibitors (8.2%‐17.8%), very strong topical corticosteroids (26.0%‐40.6%), strongest topical corticosteroids (3.5%‐7.8%), cyclosporine (0.01%‐0.3%), or phototherapy (0.06%‐1.8%) increased, and the proportion of patients who received topical non‐steroidal anti‐inflammatory drugs (12.0%‐3.1%) decreased. Annual costs for medication associated with AD per person/visit increased between 2005 and 2017; however, the ratio of medication to total cost did not. Conclusions The results of this analysis show that Japanese patients used increasingly potent treatments for AD, and overall AD‐related medication costs increased between 2005 and 2017.